The Strategic Use of an Immunomodulatory Feed Additive in Supplements for Grazing Young Nellore Bulls Transported after Weaning: Performance, Physiological, and Stress Parameters - Batista, Luis Henrique Curcino [UNESP]; Oliveira, Ivanna Morais; Prados, Laura Franco; Araújo, Laylles Costa [UNESP]; Ferreira, Igor Machado [UNESP]; Abreu, Mateus José Inácio de [UNESP]; Almeida, Saulo Teixeira Rodrigues de [UNESP]; Borges, César Aparecido de Araújo; Siqueira, Gustavo Rezende [UNESP]; Resende, Flávio Dutra de [UNESP] (My University, 2023)
The objective of this study was to evaluate four different feeding strategies using an immunomodulatory feed additive for newly weaned Nellore cattle, before and after road transport, on their physiological parameters and performances during the growing phase of pastures. In total, eighty-four young Nellore bulls (initial BW = 174 ± 11 kg; 7 ± 1 months of age) were blocked by their initial body weights 42 days before road transport (d −42) and randomly assigned to one of the four supplementation strategies. The treatments were: (1) Control (CON): no immunomodulatory feed additive (NUTRA) supplementation; (2) NUTRA pre: the inclusion of NUTRA only in the pre-transport period (d −42 to d 0); (3) NUTRA post: the inclusion of NUTRA for 42 days, only in the post-transport period (d 0 to d 42); and (4) NUTRA growth: the inclusion of NUTRA during the whole experimental period (d −42 to d 210). On d 0, the calves were transported on dirty roads in a commercial livestock trailer for 200 km (8 h). There was no effect of the treatments on the animal performance or the physiological parameters in their plasma. However, there were effects on the day of the blood sampling for all the parameters. The highest concentration of cortisol was observed on d 3 post-transport (129 ng/mL) and this decreased over time (22.4 ng/mL; d 210). On the other hand, their glucose peaked at unloading, with lower concentrations on d 7 and d 14. Their total protein concentrations increased from d 0 to d 7. The immunomodulatory feed additive supplementation at 10 g/100 kg BW/day did not modulate the physiological responses in their plasma and did not influence the performance of the Nellore bulls during the growing phase of their pastures.
Keywords: Bos indicus; NutraGen; stress; supplementation; weaned calves